(untitled) (Communication & Society, 2023)
In a climate of increasing social and political polarisation, there is much interest in dialogue and bridging differences. This article investigates the dramatisation of dialogic conflict resolution, examining how the psychological science of bridging differences can be utilised to create realistic and emotionally engaging narratives that highlight the transformative impact of dialogue on character development and relational dynamics. Relational conflicts have long been recognised as possible catalysts for character transformation, and complex narratives (Mittell, 2015) are particularly appropriate for a nuanced representation of characters’ psychological experiences throughout the process. This study draws upon extensive psychological and communication research on bridging differences compiled by Shigeoka et al. (2020) and UC Berkeley’s Greater Good Science Center (2021). It reorganises this research into a horizontal timeline of behaviours, highlighting their practical application during the conflict resolution process. It then makes a cognitive poetics analysis of how these behaviours may be observed in a case study of relational conflict from the complex television series This is Us (NBC, 2016-2022). By observing the impact these behaviours have on the transformation of characters, the study explores how credible dialogic relational conflicts can lead to verisimilar character transformation on screen. In addition, it considers how an artistic interpretation of the science of bridging differences can contribute to our understanding of dialogue in practice.